Stabilization of high-temperature cubic phase at RT in NiCr2-xFexO4 (x = 0-0.2) nanoparticles: Structural and optical studies - Pandey G.C.; Rath C. (My University, 2025)
NiCr2-xFexO4 (x = 0, 0.1 and 0.2) nanoparticles successfully synthesized by co-precipitation technique demonstrate pure cubic phase with space group Fd-3m. The high-temperature cubic phase observed at 320 K in bulk NiCr2O4 is stabilized at the room temperature (RT) by reducing the particle size to nanometer and is maintained even after incorporating Fe in NiCr2O4 lattice. The average crystallite size of the nanoparticles calculated using Scherer's formula is found to be in the range of 38-42 nm. The Williamson-Hall analysis demonstrates the decrease in lattice strain with increasing Fe concentration. FT-IR spectra further confirm the spinel structure showing two prominent stretching vibrations at around 470 cm-1 and 590 cm-1. The band gap of NiCr2-xFexO4 (x = 0, 0.1 and 0.2) nanoparticles determined from absorption in UV region is found to be 1.72 eV, 1.68 eV, and 1.66 eV, respectively. The band gap in visible region offers the possibility of utilizing these nanoparticles as photocatalyst. © 2020 American Institute of Physics Inc.. All rights reserved.